A figure of Nirutti - Temples of India Project Team (Jio Institute, 2024)
A figure of Nirutti stands prominently with a noticeable phallus, symbolizing his association with fertility and vitality. In his hands, Nirutti holds a damru (drum), a khetaka (shield), and a musala (pestle). At the bottom left, a broken animal is depicted. Nirutti’s distinctive high-raised hairdo adds to his unique presence, while his adorned appearance with jewels and a long garland underscores his divine status.